Stanley's beauty contest - Bailey, Linda, 1948- (Kids Can Press, 2009)
Stanley's people are so preoccupied with primping him for the dog show in the park that they forgot his breakfast and soon he and his dogfriends are determined to eat the show's grand prize--the biggest, most scrumptious-smelling dog cookie ever!